How Experts View the Legal System’s Use of Scientific Evidence - Diamond, Shari Seidman; Lempert, Richard (Science and Technology Law Review, 2025)
Legal scholars and courts frequently write about how scientific evidence is vetted and presented in legal proceedings, but the views of experts themselves have received little attention. Our research aims to fill that gap. This paper reports some of what we learned from a series of surveys we conducted, beginning with a survey in 2016 of scientists who had been elected to membership in the American Academy of Arts and Sciences. Subsequent surveys were directed to subscribers of the journal Science who identified as scientists and engineers and to self-identified experts who advertised their availability as experts to lawyers or appeared in the expert listings on Westlaw. Responses from those surveyed capture how they regard key actors in the legal system (Judges, Jurors, Lawyers, Other Experts) as well as the weaknesses these experts see in how the legal system treats scientists and handles scientific evidence. We also examine the extent to which expert evaluations of these issues are mediated by their experience in testifying in legal proceedings.